How Isaiah became an author : prophecy, authority, and attribution - Davage, David Willgren, 1983- (Fortress Press, 2022)
"In How Isaiah Became an Author, David Davage places the 'book' of Isaiah in the context of ancient conceptions of authorship and traces the complex process by which paratextual information in the prophecy--which originally portrayed the prophet as a link in a chain of transmission--was reimagined into a statement about the book's origins." --